De-authorization of Religion during Covid-19 Pandemic: How the Government Policies and Religious Leaders Reduced Islamic Religious in Indonesia - M. Syamsurrijal; Achmad Nurmandi; Hasse Jubba; Mega Hidayati; Bambang Hariyanto (UIN Sunan Gunung Djati Bandung, 2022)
Policies issued by the Government and religious authorities during the Covid-19 pandemic in Indonesia have resulted in the de-authorization of the structure of the pattern of carrying out religious rituals that are already established and sacred in the community. This study aims to explore government policies and religious leaders' authorities in reducing the doctrine of communal religious rituals during the Covid-19 in Indonesia. This study qualitatively investigates various forms of government policies and religious leaders during the Covid-19 pandemic – via the internet related to government policies and the appeals of religious leaders during the Covid-19. Data collection is done by observation, documentation, and literature study. Data analysis used descriptive qualitative analysis through the NVivo-12 plus application. The results of this study indicate that there has been a reduction in religious doctrine in the form of prohibiting the practice of religious rituals carried out communally in mosques and public spaces.